Answer:
A
Step-by-step explanation:
m=y2-y1/x2-x1
4-2=2
6-3=3
2/3
hope this helps =3
Answer:
The answer is 2/3
Step-by-step explanation:
Solve the following equation for b: -6 (-3-b) = 18 + 6b
Answer:
Hope this helped you
PLEASE MARK AS THE BRAINLIEST (ㆁωㆁ)
Answer:
b = 0
Step-by-step explanation:
-6 (-3-b) = 18 + 6b
18 + 6b = 18 + 6b
b = 0
Evaluate f(x)=2x-7 when x=-2,0 and 3
Answer:
Step-by-step explanation:
A) y = 2x – 7 and f(x) = 7 – 2x
Incorrect. These equations look similar but are not the same. The first has a slope of 2 and a y-intercept of −7. The second function has a slope of −2 and a y-intercept of 7. It slopes in the opposite direction. They do not produce the same graph, so they are not the same function. The correct answer is f(x) = 3x2 + 5 and y = 3x2 + 5.
B) 3x = y – 2 and f(x) = 3x – 2
Incorrect. These equations represent two different functions. If you rewrite the first equation in terms of y, you’ll find the equation of the function is y = 3x + 2. The correct answer is f(x) = 3x2 + 5 and y = 3x2 + 5.
C) f(x) = 3x2 + 5 and y = 3x2 + 5
Correct. The expressions that follow f(x) = and y = are the same, so these are two different ways to write the same function: f(x) = 3x2 + 5 and y = 3x2 + 5.
D) None of the above
Incorrect. Look at the expressions that follow f(x) = and y =. If the expressions are the same, then the equations represent the same exact function. The correct answer is f(x) = 3x2 + 5 and y = 3x2 + 5.
Convert 3 2/3 as a decimal?? Helppp
Answer: 3.66666667
Step-by-step explanation:
i need one to solve this please
Given sin A = and cos B = where A and B are both acute,
the exact value of cos(A - B)
Identify ZABF by clicking and dragging the small yellow dots to shade the
angle.
Polynomials question.
PLEASE EXPLAIN YOUR ANSWER
Answer:
9x^2-24x+16
Step-by-step explanation:
(3x-4)(3x-4)
FOIL
9x^2-12x-12x+16
9x^2-24x+16
what fraction represents a repeating fraction?
a) 4/5
B) 1/2
C) 3/4
D) 5/6
please explain too!!
D) 5/6 as 5/6 = 0.833333333333333 and the three will keep repeating
Answer:
D.
Step-by-step explanation:
You meant which one is a repeating decimal.
Okay to find out you would have to divide each.
4 divided by 5 = 0.8
1 divided by 2 = 0.5
3 divided by 4 = 0.75
5 divided by 6 = 0.833333333...
See how the three keeps on repeating? That makes it a repeating decimal.
Hope this helps!!
Martin is interested in the new hypermiling movement which focuses on getting the best miles per gallon (MPG) when driving. He gathered
some data about the weights, In thousands of pounds, of different cars and thelr average MPG. The graph below shows the results of Martin's research.
Answer:
Step-by-step explanation:
D the situation shows correlation with causation
Answer:
the situation shows correlation with caution
The difference of twice a number and 3 is at most -21
Answer:
The equation: 2n - 3 ≤ -21
The answer to the equation: n ≤ 9
Step-by-step explanation:
How to get the equation:
The difference of symbolizes subtraction. Because we are subtracting twice a number and 3, the first part of the equation can be written as 2n - 3. The n symbolizes the number.
is at most symbolizes a less than or equal to sign. That sign is ≤. And what is it less than or equal to? -21.
Now are equation is 2n - 3 ≤ -21
How to solve it:
2n - 3 ≤ -21
Add 3 to both sides of the equation
2n ≤ 18
Divide both sides of the equation by 2
n ≤ 9
On Monday, Jason ran x miles. On Tuesday, he ran 5 fewer miles than on Monday. The total number of miles Jason ran over these two days can be found using 2x−5 .
What does the "2" represent in the expression 2x−5 ?
the number of miles Jason ran on Tuesday
how many fewer miles Jason ran on Tuesday
the total number of miles ran
the number of days
Answer:
The number of days
Step-by-step explanation:
Can someone help me plz
Answer:
81 is d answer
Step-by-step explanation:
x = 9y
= > 9y + y = 90 substitution
= > y = 9
x =9y = 81 degree
10 times the sum of half a number x and 4 is 6
Answer:
-10.4
Step-by-step explanation:
Assume that the number we are looking for is x.
Now, we want to get 10 times the sum of half the number and 6 and equate this expression to 8. Then we can solve for x
step by step
half the number is 0.5x
the sum of half the number and 6 is 0.5x + 6
10 times the sum of half the number and 6 is 10(0.5x +6)
10 times the sum of half the number and 6 equals 8 is 10(0.5x+6) = 8
Now solve for x
10(0.5x + 6) = 8
5x + 60 = 8
5x = 8 - 60
5x = -52
x = -52/5
x = -10.4
Whick equation describes the line that passes through (-3, 1) and is parallel to the line y = 4x + 1?
Answer:
y = 4x + 13
Step-by-step explanation:
First of all, if they are parallel, they must have the same slope, so the 4x is the same. all we need to do now is to change the b to make it cross the point (-3, 1). Doing so, we see that the y-intercept becomes 13. Therefore, the equation is y = 4x + 13.
2000x100 guesss yall
Answer:
200,000
Step-by-step explanation:
Simplify
(sec ∅ - 1)(sec ∅+ 1)
Answer:
[tex]tan^2(x)[/tex]
Step-by-step explanation:
[tex](sec(x)-1)(sec(x)+1)\\sec^2(x) - 1\\\frac{1}{cos^2(x)} -1\\\frac{1-cos^2(x)}{cos^2(x)} \\\frac{sin^2(x)}{cos^2(x)}\\ \\tan^2(x)[/tex]
A number line going from negative 1 to positive 1 in increments of 1. There are 4 equal spaces between each number. The line contains negative 1, A, B, C, 0, D, E, F, 1. Which statements are correct? Check all that apply. Point A is plotted at –0.25. Point B is plotted at Negative one-half. Point C is an integer. Point D is a rational number. Point F is plotted at Three-fourths.
Answer:
The right choices are
Point B is plotted at negative one-half.
Point D is a rational number.
Point F is plotted at three-fourths.
Step-by-step explanation:
Let's make a number line according to the given situation. That would help us to answer the problem.
From the diagram,
Point B is plotted at negative one-half.
Point D is a rational number.
Point F is plotted at three-fourths are correct!
Answer
Point B is plotted at .Point D is a rational number.Point F is plotted at .
Step-by-step explanation:
4. Find the product. Simplify
your answer.
(5x + 1)(5x - 1)
Answer:
25x² - 1
Step-by-step explanation:
Given
(5x + 1)(5x - 1)
Each term in the second factor is multiplied by each term in the first factor, that is
5x(5x - 1) + 1(5x - 1) ← distribute both parenthesis
= 25x² - 5x + 5x - 1 ← collect like terms
= 25x² - 1
1) Find the GCF of the pair of Numbers
24 and 60
Answer:
12
Step-by-step explanation:
bruh i searched it up
Answer:
12
Step-by-step explanation:
Can you Help me please :/
Answer:
(2,1)
Step-by-step explanation:
multiply by negative three on the first equation then solve
Answer:
(-2, 1)
Step-by-step explanation:
Given:
2x+8y=4...(1)
6x-y=-13...(2)
You would want to have an x or a y value that equals the same in both equations. In this case, we can multiply equation 1 by 3 so that both x's in each equation equal 6x.
(2x+8y=4) x 3...(1)
6x-y=-13...(2)
becomes...
6x+24y=12...(3)
6x-y=-13...(4)
As you can see here, both x's in this equation are equal.
Now we will be combining these equations together. Take the equal x values and make sure they will equal 0. You do that by either subtracting the entire equation or adding it. In this problem, we will be subtracting it because 6x-6x=0
(6x+24y=12) - (6x-y=-13) = 25y =25
Now that we can solve for y separately, 25y=25 y=1
To solve for x, just substitute y into one of the original equations (equations 1 or 2). For this problem, I'll use equation 1.
6x-y=-13
6x-1=-13
6x=-12
x=-2
(This is what I got for my answer and here is the explanation. I apologize if my answer is incorrect. If someone notices a mistake in my answer, please correct me, thank you and have a nice day!)
Write the equation of a line that is parallel to y=2/3x+7 and goes through the point (6,9).
Answer:
m1=m2 condition for parallelism
m1=m2= 2/3
= y-7/x_6
y=2/3x +3
what is 8 1 2 times 11
Answer:
[tex]8\frac{1}{2}*11=93\frac{1}{2}[/tex]
Step-by-step explanation:
Simplify the expression.
please Solve
9(x - 11) = 9
Answer:
9(x-11) = 9
9x-99 = 9
9x = 108
x = 108/9
thus,
x = 12
-15=10x-40x
what does x equal to
Answer:
0.5
Step-by-step explanation:
-15=-30x
-15/-30=0.5
Peter spends Atmos $30 at the bowling alley he spends five dollars for each show rental and soda soda and each game cost two dollars
Answer:
chicken nuggets
Step-by-step explanation:
Answer:
If you want to write an equation it would be 5x+2x=30
Step-by-step explanation:
I am assuming you want an equation, if you do not, just reply to this
4 less than a number g equals 9
Answer fast I will name you the most Brainly please help
9514 1404 393
Answer:
g - 4 = 9
Step-by-step explanation:
If the number is g, then four less than the number is g-4.
If that is 9, then you have the equation ...
g - 4 = 9
_____
Additional comment
If you add 4 to both sides of the equation, you have its solution.
g -4 +4 = 9 +4
g = 13
So, 4 less than 13 is 9.
A store has 4 employees that earn 178 dollars altogether if they all earn the same amount how much does each employee earn
Answer:
Each employee earns $44.50
Step-by-step explanation:
When you divide $178 evenly among 4 employees, each will get $44.50.
178÷4= 44.50
Check: 44.5×4= 178
A frying pan has a diameter
of 14 cm. We are making a
pancake and want to know
the biggest pancake we can
make.
Answer:
this is the exact same question I need too
Well if the frying pan has a diameter of 14cm you would need to multiply 14 by 4 or the number of edges your pan/ platter has. Then you know the diamter of the pancake you would be able to make.
Hope I helped! Please let me know in the comments below if this helped you to find your pancake diamete! I personally love pancakes and I am also a huge fan of math and estimating!
If I helped please rate, thanks, and mark me brainliest.
Yours,
Fellow brainiac
Plz help me I’ll give brainliest
Answer: (below)
Step-by-step explanation:
y = 2x + 1
slope = 2
y-int = (0, 1)
y = 3x - 1
slope = 3
y-int = (0, -1)
y = 4x
slope = 4
y-int = (0, 0)
y = -3x - 1
slope = -3
y-int = (0, -1)
y = -x - 4
slope = -1
y-int = (0, -4)
y = (2/5)x - 1
slope = 2/5
y-int = (0, -1)
7 - 3(5x - 10) - 67
Answer:
−15x+−30
Step-by-step explanation:
Distribute:
=7+(−3)(5x)+(−3)(−10)+−67
=7+−15x+30+−67
Combine Like Terms:
=7+−15x+30+−67
=(−15x)+(7+30+−67)
=−15x+−30
Answer:
Step-by-step explanation:
66
Just need a lil help with this
Answer:
36 cm
Step-by-step explanation: